Hormones Effect on Gyrinops versteegii (Gilg.) Domke Shoots Cutting using Water Rooting Method - Y.M.M Anita Nugraheni; Kurniawati Purwaka Putri (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2018)
Gyrinops versteegii is one of protected species because of the rare existence. One of the efforts to keep the preserved is by cultivation. Cultivation techniques using generative basis has already done a lot. However, this technique has several limitations, due to the recalcitrant character of the seeds and the inequality of the characteristics of the progeny with their parent. Meanwhile, vegetative techniques will produce a new individual that have the same characteristics as the parent. The alternative-promising vegetative techniques of G. versteegii are using media because it is cheap and easy to obtain, and increase the achievement if additional hormones were used. The purpose of this research is to determine the optimum concentration of the NAA hormone for G. versteegii cuttings. The research method is done by cutting the saplings of G. versteegii on the shoots. The medium used are water without hormones (as control), water with hormones of NAA 100, 200, and 300 ppm. Observations 10 times, at the end of the observation carried out measurements on the root, percent of life, buds, dry stem weight, and dry root weight. The result showed that NAA hormone treatment influenced significantly on the growth of the roots, percent of life, dry stem weight and dry weight of roots of G. versteegii. Medium of water with the addition of NAA 300 ppm was the composition that can be used as a medium to trigger initial rooting.